Emerging multidrug resistance isolates of hospital‐acquired bacterial meningitis in a tertiary care centre in North India. Issue 11 (November 2019) - Raza, M. S.; Das, B. K.; Goyal, V.; Lodha, R.; Chaudhry, R.; Sood, S.; Gautam, H.; Sreenivas, V.; Nair, D.; Mohapatra, S.; Kapil, A.
Abstract : Purpose. : Acute bacterial meningitis continues to be a potentially life threatening condition. Hospital‐acquired meningitis is rapidly increasing and adding an immense burden to the health system due to the emergence of multidrug resistance isolates. The purpose of this study is to find the antibiotic susceptibility pattern of the bacteria detected from hospital‐ and community‐acquired meningitis. Methodology. : A total of 400 Cerebrospinal fluid (CSF) samples from the suspected meningitis cases were collected and processed for cell count, biochemical examination, Gram staining, latex agglutination and culture. Bacteria grown on blood, chocolate and Mac‐conkey agar were identified by matrix‐assisted laser desorption/ionization‐time of flight. Antibiotic susceptibility tests were performed as per Clinical and Laboratory Standard Institute guidelines. Results. : Of the isolates, most prevalent Gram negative organisms in hospital‐acquired bacterial meningitis were Escherichia coli 13 (27.08%), Acinetobacter baumannii 12 (25%), Klebsiella pneumoniae 5 (10.42%), Pseudomonas aeruginosa 4 (8.33%) and Gram positive organisms were Staphylococcus aureus 4 (8.33%), Enterococcus faecium 3 (6.25%) and CONS 2 (4.16%). Streptococcus pneumoniae 3 (6.25%) was the predominant organism in community‐acquired bacterial meningitis. All the Gram negative isolates were multidrug resistance. Only colistin and imipenem were effective antibiotics against them. Likewise Gram positive organisms were susceptible to most of the antibiotics tested. However, E. faecium was only susceptible to Vanco+Teicoplanin. Conclusion. : In hospital‐acquired bacterial meningitis, multidrug resistance Gram negative bacteria are a huge challenge for the treatment of patients. Hence, antimicrobial stewardship should be followed to counteract with the emerging multidrug resistance isolates.